EFFECTS OF PSIDIUM GUAJAVA AQUEOUS EXTRACTS ON HAEMATOLOGICAL PROFILE AND SERUM LIPID VARIABLES OF ALBINO RATS - KULLU, ARUNA ROSHNI; TABASSUM , WAZIDA; M. P. SINHA (The Bioscan, 2013)
The effect of aqueous extract of leaves on some haematological and serum lipid parameters in rats during a seven day administration of the doses of 250mg/kg and 500 mg/kg body weight orally was investigated. The parameters evaluated include serum lipids, red and white blood cell indices. The results show that the extract administered significantly increased (p<0.05) packed cell volume, haemoglobin concentration, red blood cell, MCH, MCHC, MCV and platelet count t at the dose of 250mg /kg and 500 mg/kg body weight when compared with control. Whereas Psidium guajava the platelet was significantly increased (p<0.05) at 250mg/kg body weight but at 500mg/kg body weight the count significanty reduced (p<0.05). Also, the extract significantly increased (p<0.05) white blood cell count at all doses administered when compared with control. Moreover, the extract significantly reduced (p<0.05) total cholesterol concentration, triglycerides and HDL-cholesterol concentration in the serum while it had no significant effect on serum LDL-cholesterol concentration at all doses administered when compared with controls. The results of this study suggest that the extract may have beneficial effect on serum cholesterol concentration and triglycerides reduction as well as in anemia and immunity dependent disorders.